Pre-Existing Mutations in the Rilpivirine Phase Iii Trials Echo and Thrive: Prevalence and Impact on Virological Response. Issue 2 (February 2013) - Vingerhoets, Johan; Rimsky, Laurence; Van Eygen, Veerle; Nijs, Steven; Vanveggel, Simon; Boven, Katia; Picchio, Gaston
Background: Rilpivirine (RPV), a non-nucleoside reverse transcriptase inhibitor (NNRTI), was approved for HIV-1 infected, antiretroviral treatment-naive adults based on data from two Phase III trials. In the screening population, the prevalence of 49 NNRTI resistance-associated mutations (RAMs) and the impact of allowed NNRTI RAMs on virological response to an RPV- or efavirenz (EFV)-containing regimen were analysed. Methods: ECHO and THRIVE were global, Phase III, double-blind, double-dummy, randomized trials in antiretroviral treatment-naive, HIV-1-infected adults to determine whether RPV 25 mg once daily had non-inferior efficacy versus EFV 600 mg once daily, both given with tenofovir/ emtricitabine (ECHO) or tenofovir/emtricitabine, zidovudine/lamivudine or abacavir/lamivudine (THRIVE). The prevalence of 49 NNRTI RAMs, including the predefined list of 39 NNRTI RAMs used to exclude patients with potential resistance to RPV or EFV, was investigated at screening by population sequencing (including mixtures) using the virco®TYPE HIV-1 genotyping assay. Results: Of the 1, 796 screened patients in whom genotypic resistance results were available, 372 (21%) had NNRTI RAMs. Of 527 screening failures, 148 (28%) were due to the presence of NNRTI RAMs. The presence of allowed NNRTI RAMs was associated with comparable response rates to the overall population (RPV 84.3% versus EFV 82.3%, intent-to-treat time-to-loss-of-virological-response): V90I (82.4% and 100% for RPV and EFV, respectively), V106I (85.7% and 93.3%), V179I (87.7% and 94.0%) and V189I (100.0% and 88.9%). Conclusions: Analysis of the ECHO and THRIVE screened population suggests that transmitted NNRTI resistance is prevalent in treatment-naive patients but prevalence of the 15 RPV RAMs remains low. The four allowed NNRTI RAMs present at baseline did not affect RPV response at week 48. Virus Drug Resistance and Curative Strategies (Los Cabos, Mexico, 7–11 June 2011, abstract 41).